Safety and security review for the process industries : application of HAZOP, PHA, what-if and SVA reviews - Nolan, Dennis P. (Gulf Publishing Company, 2014)
Dennis Nolan, drawing on decades of experience as a well-known safety author and senior loss prevention specialist at Saudi Aramco, provides the essential procedures and checklists in Safety and Security Review for the Process Industries. In addition to guiding the reader through the selection and execution of efficient and complete hazard analysis and safety reviews (such as HAZOP, PHA, What-If, SVA, LOPA, Bowtie), Nolan shares his personal experience and illustrates procedures with real-world examples. Updated throughout to reflect changing practices, the fourth edition expands its scope.